PEMBUATAN FILE SYSTEM GLUSTERFS DISTRIBUTED- REPLICATED VOLUME DI SEKOLAH VOKASI IPB UNIVERSITY - Aep Setiawan; Rifa Ade Rahmah (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
College of Vocational IPB University (SV-IPB) uses a client-server system as an information technology architecture. The server provides several services that are used to assist the teaching and learning process at the IPB Vocational School. The application used to provide services is the Modular Object-Oriented Dynamic Learning Environment (MOODLE) which is used for e-learning. SV-IPB provides two Virtual Machines which are used as a web server and a database server. The use of a single web server to replace the request is certainly less stable because there is no web server to back it up so that the service will stop. This situation states that the use of a single web server does not have high information (high available). To overcome this problem, the cluster technology can be used to group several web servers in SV-IPB. The web server clustering technology used is the Gluster File System (GlusterFS) with the volume type used, namely Distributed-replicated volume. Based on the tests that have been carried out, this project can solve the problem that has been described earlier that